2008
DOI: 10.1002/da.20278
|View full text |Cite
|
Sign up to set email alerts
|

Obstetrician-gynecologists' screening patterns for anxiety during pregnancy

Abstract: As obstetrician-gynecologists (ob-gyns) take on a greater role in women's healthcare, it is important that they are aware of the high prevalence of anxiety disorders in their patient population. Anxiety disorders present during pregnancy can have detrimental effects on both mother and child. In this study, we queried 1,193 ob-gyns on their screening rates, practice patterns, training, and knowledge as they relate to anxiety disorders during pregnancy. We achieved a 44% response rate (n=397) after three mailing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 39 publications
(43 reference statements)
0
27
0
Order By: Relevance
“…Demographic data are reported elsewhere [12]. In summary, 51% of respondents were female and 49% were male, they had been in practice an average of 14.4 years (SD ¼ 9.3), and they considered themselves either specialist (44%) or both primary care physician and specialist (55%).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Demographic data are reported elsewhere [12]. In summary, 51% of respondents were female and 49% were male, they had been in practice an average of 14.4 years (SD ¼ 9.3), and they considered themselves either specialist (44%) or both primary care physician and specialist (55%).…”
Section: Resultsmentioning
confidence: 98%
“…This questionnaire was utilized in another study assessing anxiety screening patterns during pregnancy [12]. There were three mailings of the survey, beginning in November 2005.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite growing awareness, it is noted that health care providers' detection of psychological distress during pregnancy remains low (Bennett et al, 2004a;Coleman, Carter, Morgan, & Schulkin, 2008). Additionally, the effectiveness of commonly prescribed treatment regimes, such as pharmacotherapy or psychotherapy, is frequently reported as being sub-optimal (Marcus & Flynn, 2007).…”
Section: Psychological Health During Pregnancymentioning
confidence: 99%
“…Another reason why feelings of anxiety or depressed mood may go unrecognized is a lack of screening by care providers. A study by Coleman et al (2008) found that only 20% of physician respondents screen for anxiety during pregnancy.…”
Section: Detection and Treatmentmentioning
confidence: 99%